Fuzzy clustering algorithm to identify the effects of some soil parameters on mechanical aspects of soil and wheat yield - Servadio, Pieranna; Verotti, Matteo (Spanish Journal of Agricultural Research, 2018)
In this paper, site-specific management zones (MZs) were delineated in three fields belonging to a farm in the center of Italy and characterized by different soil texture. Crop yield and various soil parameters, both physical (soil structural stability, clay fraction, water content, and organic matter) and mechanical (shear strength and penetration resistance) were monitored. Yield data were acquired by means of a combine harvester equipped with a precision land management system during three consecutive growing seasons. At the end of the third growing season, soil properties were investigated by means of georeferenced soil sampling. After data gathering, a fuzzy clustering algorithm was applied to define management zones. Results highlighted spatial variability between the three fields and temporal variability between the three consecutive growing seasons. Whilst the latter could be ascribed to the rainfall distribution (therefore moisture could be considered as a limiting factor in wheat growth), the delineated MZs suggest that clay content and organic matter could affect both mechanical parameters of soil and crop yield. The defined MZs can serve as a basis to generate prescription maps for variable-rate application inputs and variable tillage.